Correlation between maternal weight gain and birth weight among term babies - Singh, Umesh; Acharya, Indira (Journal of Nepal Paediatric Society, 2022)
Introduction: Healthy and well-nourished mother is likely to give birth to a healthy normal child with adequate birth weight. We aimed to determine the correlation of gestational weight gain and newborn’s birth weight. Methods: We studied participant-level data for 295 pregnant women coming for delivery services between January 2018 and December 2020 at Shree Birendra Hospital, Chhauni, Kathmandu, Nepal. A retrospective data of pre-pregnancy body mass index, maternal weight gain during different trimesters of pregnancy were collected. The prevalence of small and large for gestational babies were compared with mother’s weight gain according to Institute of Medicine (IOM) guidelines. Pearson test was used to assess the correlation between gross maternal weight gain during pregnancy and birth weight. Results: Among 295 women, 12.2% underweight, 55.6% normal weight, 26.1% overweight and 6.1% were obese. The overall mean gestational weight gain (GWG) was 11.78 kg. Birth weight of the babies ranged from 1500 gm to 5100 gm with mean weight of 3148 gm. Majority of small for gestational age and large for gestational babies were seen among women below and above IOM guidelines respectively. Conclusions: Findings from this study suggest that maternal weight gain during pregnancy increases the birth weight. Across all BMI categories, insufficient GWG is associated with slightly increased risk of SGA, while relative risk of LGA is higher in excess GWG group.